KEKUATAN PEREMPUAN DALAM AYAT-AYAT HUKUM KEWARISAN - Nuzul Iskandar (Kafa`ah: Journal of Gender Studies, 2015)
Dialogue about the position of women in Islam become stronger because of the campaign launched by women activists. One of the theme that strengthen against Islam is about the distribution of inheritance is considered ignoring the interests of women. This paper is intended as an attempt to re-read the text used as a basis for decision making with regard to inheritance law. Rereading not deny formulations contained in the books of fiqh, but rather an attempt to open discourse and develop Islamic science more relevant and contextual. From reading the verses of inheritance, namely Q.S. 04: 11-12, can s lower than men. Second, the focus point or benchmark heritage be found that: first, a quota for women's inheritance is not necessarily alway paragraph it is not men, but women